Topological methods in data analysis and visualization / 6 Topological methods in data Analysis and visualization VI : theory, applications, and software / Ingrid Hotz, Talha Bin Masood, Filip Sadlo, Julien Tierny (editors) - Hotz, Ingrid; Bin Masood, Talha; Sadlo, Filip; Tierny, Julien (Topological methods in data analysis and visualization, 2021)
Scalar Field Topology–Algorithms and Applications -- W-Structures in Contour Trees -- Treemap Based Exploration of Merge Trees -- Notes on Percolation Analysis of Sampled Scalar Fields -- Distributed Task-Parallel Topology-Controlled Volume Rendering -- Topology-Based Tracking of Multi-Center Cyclones -- Using Contour Trees in the Analysis and Visualization of Radio Astronomy Data Cubes -- Topological Methods in Complex Fields–Flow Fields, Tensor Fields, and Multi-ﬁelds -- Objective Finite-Time Flow Topology from Flowmap Expansion and Contraction -- Coreline Criteria for Inertial Particle Motion -- Implicit Visualization of 2D Vector Field Topology for Periodic Orbit Detection -- Visually Evaluating Topological Equivalence of Bounded Bivariate Fields -- Topological Feature Search in Time-Varying Multiﬁeld Data -- Tensor Fields for Data Extraction from Chart Images: Bar Charts, Histograms, and Scatter Plots -- Topology for Geometric Data -- A Fast Approximate Skeleton with Guarantees for Any Cloud of Points in a Euclidean Space -- Topologically Robust B-Spline Reconstruction of Fibers from 3D Images -- Introduction to Vector Field Topology -- An Overview of the Topology ToolKit -- Implementing Persistence-Based Clustering of Point Clouds in the Topology ToolKit -- TopoInVis TTK Hackathon: Experiences, Lessons Learned, and Perspectives.
Keywords: Konferenzschrift -- 8th TopoInVis workshop -- 06.2019 -- Nyköping